Kafka e Weber: afinidades e limites entre a interpretação literária e científica - Maciel, Weslei Pinheiro [UNIFESP] (2019)
The current work seeks to elaborate a comprehension about sociological and litterary interpretations of social reality and beyond that comprehend the touchpoints betwen such interpretations. To this end we’ll cast sight over the Works Amerika (1912) by Franz Kafka and The Protestant Ethic and the Spirit of Capitalism (1904-5;1920), Protestants Sects and the Spirit of Capitalism (1906) and Capitalism and rural society in Germany (1904) by Max Weber. The selected works, besides being contemporary works, are also result of a germanic World View, and, to a certain extent, handle about the same subject: The United States of America. When they look to America they describe as a emblematic country of the rationalization process that occurred in the West. We’ll take either literature and sociology as forms of knowledge, notwithstanding their limitations and differences with respect to “objectivity”, to comprehend the representations that each of them makes on the same theme . We will try to trace the possible dialogues and affinities between the weberian sociology and the kafkian literature through their portraits and interpretations of America.